J28 Effects of caffeine and chronobiotics on morning repeated sprint performance - Brownrigg, Ellie; Chadwick, Michael; Blow, Liv; Snowe, Hayden; Calcagni, Eddie; Durkin, Kyle; Hajdukiewicz, Dani; Porritt, George; Fernley, Jack; Middleton, Harvey; Edwards, Ben (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Gross muscular performance (lasting <6 s) is 3.4-10.2% higher in the evening when compared with early morning (17:00-19:00 vs. 06:00-10:00 h; Pullinger et al., 2019). However, there is limited research on the effect of caffeine and chronobioltics (bright light) on gross muscular performance, in the early hours of the morning. Twelve healthy, active male participants (mean±SD; age, 21 ± 2 years, body mass, 79 ± 6 kg; stature, 180 ± 5 cm) volunteered and completed 2 familiarisation sessions and 2 experimental sessions. Experimental condition 1: caffeine pill condition (ingested at 06:30 h and 2; Exposure to bright light for 1 h and exercising for the last 30-min on a cycle ergometer at 07:00 h the morning before morning performance; with dawn simulation exposure for 30-min prior to waking on the testing day. Participants retired at 22:30 and woke at 06:30 h throughout the experiment. Both sessions commence at 07:00 h. On entry to the laboratory participants were seated and after intra-aural temperature (IA) was recorded 30-min. During this time questionnaires were administrated regarding mood and prior sleep. Following this, participants then took part in several tests including agility, hand grip strength, counter movement jump and squat jumps. Agility was measured (Whitty SEM Microgate system, UK). Hand grip strength was measured using a dynamometer and squat and countermovement jump values were measured using a jump mat (best of 3 attempts). After this, participants then completed a warm-up (5-min at 10km/h on a motorised treadmill followed by a combination of stretches). Participants were then asked to complete 10 full effort sprints were time, rating of perceived exertion, heart rate and thermal comfort were recorded after each sprint during the 30 s rest. Blood glucose and lactate were also measured before exercise, post warm-up and post exercise. After 30-min participants were asked to cycle around 160 bpm. Heart rate, RPE and thermal comfort were recorded every 5-min. The aim of the study was to assess the effects of caffeine and chronobiotics (bright light/exercise and dawn simulation) on morning RSP and grip strength.